Advances in NSCLC - Bankhead, Charles (MD Conference Express, 2011)
The era of targeted therapy has arrived for lung cancer and has made an unprecedented impact on outcomes, including survival. Choosing therapy on the basis of mutation testing has dramatically increased survival expectations from a few months with conventional chemotherapy to as much as 3 years with targeted agents.